Evaluation of chemical and biological management strategies against bacterial blight of French bean (Phaseolus vulgaris) causedby Xanthomonas axonopodis pv. phaseoli - SUCHITA, SAKSHI; KANSAL, SANDEEP; PARWAN, SONALI; GUPTA, SHIVANI (The Indian Journal of Agricultural Sciences, 2025)
Bacterial blight caused by Xanthomonas axonopodis pv. phaseoli is a severe disease in French bean (Phaseolus vulgaris L.), leading to yield losses of about 10–40%, depending on the susceptibility of the cultivar and environmental conditions. The study was carried out during rainy (kharif) season of 2020 and 2021 at Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Himachal Pradesh, to evaluate the effectiveness of various management strategies, including chemical treatments and bioagents, to mitigate. Efficacy of different chemicals was evaluated under in vitro conditions using well diffusion method. The results showed streptocycline as the most potent inhibitor of Xanthomonas axonopodis pv. phaseoli showing maximum zone of inhibition (22.20 mm). Further evaluation of chemicals under pot culture experiment revealed that seed treatment using streptocycline (100 ppm) combined with three foliar sprays of copper oxychloride (0.3%) applied at 7 days interval was the most effective strategy, significantly reducing the disease severity. During the field trials the combination treatments (T6 and T7) proved most effective in reducing disease indices and increasing yield with the highest disease control and yield per hectare. Seed treatment using streptocycline (100 ppm) and spray of copper oxychloride (0.3%) (T6) provided the most robust results followed by the combination of seed treatment with streptocycline (100 ppm) and streptocycline spray (T7). These treatments not only controlled the disease effectively but also offered the best economic returns as indicated by the ICBR ratios. The findings emphasize the effectiveness of combining seed treatments and foliar sprays in controlling bacterial blight and improving French bean productivity.